Knowledge and Preparedness of Dentists in Response to Bioterrorism - Chelluri Shreya Reddy; Saba Asra; Priya Sivan Padma; Hashim Nada Tawfig; Shetty Shishir Ram; Padmanabhan Vivek; Shaga Pranathi; Pulluri Saraswathi Sravani; Bahra Shadi El (Wolters Kluwer Medknow Publications, 2024)
IntroductionIn the current climate of heightened terrorist activity, the deliberate release or threat of biological agents like viruses, bacteria, fungi, or their toxins to induce sickness or death among civilians has become a genuine possibility. The most crucial action during a bioterrorist strike is early warning. The possibility of such an occurrence in dental setting is underestimated. Methods and MaterialsSeventy five graduate students participated in the research. In a survey on zoonotic diseases, participants were asked whether they were familiar with the transmission from person to person, if the diseases caused significant morbidity and mortality, whether they were simple to produce and disseminate, and whether they posed a high risk of infection. ResultsGraph Prism was used to examine the data. A single proportion test was used to determine the "Aware Not Aware" group. The first 10 questions assessed dentists objective knowledge of bioterrorism. The importance of the last six questions was determined by their analysis of dentists' preparedness and desire to respond to a bioterrorism associated occurrence via perceived knowledge. ConclusionGiven the real danger they may face, dentists needed to be vigilant regarding the prevention, detection, and treatment of zoonotic illnesses transmitted in their offices or as a vector while being commended for their courage in the face of adversity.